Surgical treatment for functional ischemic mitral regurgitation: current options and future trends - Nicolini, Francesco; Agostinelli, Andrea; Vezzani, Antonella; Molardi, Alberto; Benassi, Filippo; Gallingani, Alan; Romano, Giorgio; Gherli, Tiziano (Acta Biomedica Atenei Parmensis, 2015)
There is an increasing number of patients with mitral regurgitation secondary to dilated cardiomyopathy. Ischemic mitral regurgitation is a common complication of left ventricular dysfunction related to chronic coronary artery disease: it is present in 10–20% of these patients and is associated with a worse prognosis also after coronary revascularization. Currently, coronary artery bypass grafting combined with restrictive annuloplasty is the most commonly performed surgical procedure, although novel approaches have been used with varying degrees of success. The suboptimal results obtained with the commonly used surgical approaches require the development of alternative surgical techniques with the aim to correct the causal mechanisms of the disease. In fact the pathophysiology of ischemic mitral regurgitation is multifactorial involving global and regional left ventricular remodeling, as well as the dysfunction and distortion of the components of the entire mitral valve apparatus. The purpose of this review is to present the current surgical techniques available for the treatment of ischemic mitral regurgitation and to discuss novel approaches to the repair of this complex disease. (www.actabiomedica.it)